Vegetation, fire, climate and human disturbance history in the southwestern Mediterranean area during the late Holocene - Jiménez-Moreno, Gonzalo; García-Alix, Antonio; Hernández-Corbalán, María Dolores; Anderson, R. Scott; Delgado-Huertas, Antonio (Quaternary Research, 2012)
Detailed pollen, charcoal, isotope and magnetic susceptibility data from an alpine lake sediment core from Sierra Nevada, southern Spain record changes in vegetation, ﬁre history and lake sedimentation since ca. 4100 cal yr BP. The proxies studied record an arid period from ca. 3800 to 3100 cal yr BP characterized by more xerophytic vegetation and lower lake levels. A humid period is recorded between ca. 3100 and 1850 cal yr BP, which occurred in two steps: (1) an increase in evergreen Quercus between 3100 and 2500 cal yr BP, indicating milder conditions than previously and (2) an increase in deciduous Quercus and higher lake levels, between ca. 2500 and 1850 cal yr BP, indicating a further increase in humidity and reduction in seasonal contrast. Humid maxima occurred during the Roman Humid Period, previously identiﬁed in other studies in the Mediterranean region. Intensiﬁed ﬁre activity at this time could be related to an increase in fuel load and/or in human disturbance. An arid period subsequently occurred between 1850 and 650 cal yr BP, though a decrease in Quercus and an increase in xerophytes. The alternation of persistent North Atlantic Oscillation modes probably played an important role in controlling these humid–arid cycles
The following values have no corresponding Zotero field: publisher: University of Washington
Keywords: climate; Fire history; Late Holocene; Roman Humid Period; Sierra Nevada; southern Spain

Characterization of semi-extensive goat production systems in southern Spain - Castel, J. M.; Mena, Y.; Delgado-Pertinez, M.; Camunez, J.; Basulto, J.; Caravaca, F.; Guzman-Guerrero, J. L.; Alcalde, M. J. (SMALL RUMINANT RESEARCH, 2003)
This study attempts to describe the semi-extensive goat fanning sector in Andalusia (south of Spain) and to establish characteristics. Eighty-nine goat farmers were surveyed in three areas of this region. The survey examined all aspects of the systems, from socio-economy to management. A multivariate analysis (multiple correspondence and cluster) was used to determine the different farm characteristics. Most of the goat farms studied are single-worker or family managed. The farmers lack training and are elderly, so that continuity of the activity is not assured, although newcomers are usually young. All the farms have some area in ownership, although the farms most specialized in dairy goat products are the smallest in both ownership and total area. The roads are generally in good condition, except on farms with little land, situated in areas of the sierra. Machine-milking installations, closely related to the presence of infrastructures and of goats with a dairy tendency, are generally lacking, (this aspect is improving day by day). Artificial nursing is less generalized than machine-milking. Farms specializing in milk production, whose main activity is dairy goat farming, have dairy specialized breed or crossbred (milk and meat) goats. Feeding depends largely on grazing, with little area being cultivated to produce feed for the goats. Little distinction is made for the production level. Olive or acorn tree branches (Quercus ilex spp.) are used as feedstuff, depending on the types of tree predominating in the area. Five farm types were established, the differences depending on 14 variables of socio-economic aspects, level of production, infrastructure and installations, and feeding. Generated information from this study entails an advance into knowledge of goat farming systems in the Mediterranean area (where little information is generated). The relevance of this study is important since Andalusia has 40% of goats in Spain that produce more than half of the total goat milk in the country, which points out the socio-economical importance for most depressed areas in the region. This work supposes previous steps for improving the semi-extensive goat farming sector. From a methodological point of view, the discussion on variable types and utility establishes farm type characteristics. (C) 2002 Elsevier Science B.V. All rights reserved.
The following values have no corresponding Zotero field: pub-location: PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS publisher: ELSEVIER SCIENCE BV
Keywords: characterization methods; goat systems; semi-extensive farming; southern Spain

Medicinal plants used in the Barros Area, Badajoz Province, Spain. - Vázquez, F. M.; Suarez, M. a; Pérez, A. (Journal of ethnopharmacology, 1997)
A study of the wild and cultivated medicinal plants used in the Barros Area (southern Spain) is reported, 48 plants distributed among 20 different families are used in the treatment of various human diseases. The use of Bellis annua L. Centaurea ornata Wild., Leuzea conifera (L.) DC., Pulicaria paludosa Link and Asparagus aphyllus L. is reported.
From Duplicate 2 (Medicinal plants used in the Barros Area, Badajoz Province, Spain. - Vázquez, F M; Suarez, M a; Pérez, A)From Duplicate 2 (Medicinal plants used in the Barros Area, Badajoz Province, Spain. - Vázquez, F M; Suarez, M a; Pérez, A)The following values have no corresponding Zotero field: accession-num: 9032619
Keywords: Data Collection; Humans; Medicinal; Medicinal plants; Medicinal: classification; Medicine; Phytotherapy; Plants; southern Spain; Spain; Structure-Activity Relationship; Traditional; Traditional phytotherapy

Estimating tree density in oak savanna-like lsquo;dehesa’ of southern Spain from SPOT data - JOFFRE, R.; LACAZE, B. (International Journal of Remote Sensing, 1993)
Abstract The main objective of this study was to establish a method of estimating tree density in savanna-like vegetation systems using the highest spatial resolution available from satellite data (SPOT-1 panchromatic = 10 m resolution) based on the assumption that for sparse trees on a contrasting herbaceous background, spatial filters may provide a direct mapping of tree cover. The study was performed in the ?dehesas? oak-woodland of southern Spain. This particular landscape is characterized by the presence of scattered evergreen oak trees (Quercus ilex and Q. suber) whose density ranges from 0 to 80 even-aged mature trees per hectare which gives the appearance of a savanna-like vegetation. Tree density can be accurately estimated by SPOT-1 panchromatic data after numerical filtering. This method allows the mapping of tree density of the dehesas, a key parameter reflecting the functional vegetation-soil-climate equilibrium which exists for both woody and herbaceous strata.
doi: 10.1080/01431169308904368doi: 10.1080/01431169308904368The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Dehesa; oak; savanna-like; SOPT data; southern Spain; tree density